Are fluctuations in physical performance affected by contextual factors in women’s handball matches? An analysis using five-minute fixed phases - García-Sánchez, Carlos; Navarro, Rafael Manuel; Nieto-Acevedo, Raúl; de la Rubia, Alfonso (Biology of Sport, 2025)
The purpose of this study was twofold: to analyse physical performance fluctuations throughout match play in women’s handball; and to investigate whether physical performance fluctuations are affected by contextual factors (i.e., level of the opponent and playing positions). Twenty-two female players from the Spanish 2 nd Division were monitored across 13 matches. Each match was divided into 5 min fixed phases. Total distance (TD), high-speed running (HSR) and PlayerLoad (PL) were collected using a local positioning system. The highest values of TD, HSR and PL were registered during the first 5 min phase of the match ( p < 0.05, moderate-large effects), while the lowest values of TD and PL were registered in the last phase of the first half and for HSR in the last phase of the match ( p < 0.001, large effects). Regarding level of the opponent, low-level teams elicited higher TD in the first 10 min of the match ( p < 0.05, moderate effects). Conversely, matches involving high-level teams registered more TD and PL in the last phase of the match ( p < 0.05, moderate effects). In relation to playing positions, wings showed the highest physical performance in all 5 min phases of the match, whereas the pivots showed the lowest physical performance. In the present study the physical performance decreased throughout the match and the fluctuations were strongly affected by the level of the opponent and playing positions. Therefore, handball coaches should incorporate strategies to mitigate fatigue within and between halves.